Analysis of Cardiotoxicity and Risk Factors of Breast Cancer Chemotherapy Drugs: A Five-Year Single-Centre Retrospective Study in Early Breast Cancer - Ju F; Gu H; Yu L; Zhao G; Liu Y; Yin D; Niu J; Xue T; Yin C; Jiao L; Li C; Wu J; et al. (Drug Design, Development and Therapy, 2025)
Feng Ju,1,* Hong Gu,1,* Lijiang Yu,2 Guangyu Zhao,1 Yin Liu,1 Dengyang Yin,1 Jiali Niu,1 Ting Xue,1 Chunxia Yin,1 Lingyun Jiao,1 Chaoqun Li,1 Jian Wu,3 Yong Ji4 1Department of Pharmaceutical Administration, Jingjiang People’s Hospital Affiliated to Yangzhou University, Jingjiang, Jiangsu, 214500, People’s Republic of China; 2Department of Oncology, Jingjiang People’s Hospital Affiliated to Yangzhou University, Jingjiang, Jiangsu, 214500, People’s Republic of China; 3Department of Rehabilitation, Jingjiang People’s Hospital Affiliated to Yangzhou University, Jingjiang, Jiangsu, 214500, People’s Republic of China; 4Department of General Surgery, Jingjiang People’s Hospital Affiliated to Yangzhou University, Jingjiang, Jiangsu, 214500, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian Wu, Department of Rehabilitation, Jingjiang People’s Hospital Affiliated to Yangzhou University, No. 28, Zhongzhou Road, Jingjiang, Jiangsu, 214500, People’s Republic of China, Tel +86 0523-84995225, Email wu_wuwujianhh1201@21cn.com Yong Ji, Department of General Surgery, Jingjiang People’s Hospital Affiliated to Yangzhou University, No. 28, Zhongzhou Road, Jingjiang, Jiangsu, 214500, People’s Republic of China, Tel +86 0523-84995225, Email jiyong_jy615@163.comObjective: To investigate the cardiotoxicity of breast cancer (BC) chemotherapy drugs and analyse their risk factors.Methods: Through the electronic medical record system, the data of 415 patients with early BC (EBC) who had undergone a complete chemotherapy cycle were retrospectively collected within 5 years from the beginning of chemotherapy. Baseline clinical, biochemical and echocardiographic data were retrospectively extracted for comparative analysis.Results: The incidence of cardiotoxic events in patients with EBC receiving trastuzumab-targeted therapy was as high as 23%, which was significantly higher than that in the conventional chemotherapy group (P = 0.006). The incidence of cardiotoxicity in patients receiving conventional chemotherapy combined with targeted therapy increased year by year. The use of anthracyclines or trastuzumab significantly increased the risk of cardiotoxicity, especially when the two drugs were used in combination, showing a significant synergistic effect (P < 0.001). An anthracycline exposure cycle > 4, radiotherapy, use of trastuzumab, abnormal myocardial zymogram and elevated troponin I (TnI) levels were identified as risk factors for cardiotoxicity. The Tei index increased over time (P < 0.001), indicating progressive subclinical cardiac dysfunction. The Tei index of patients after 4 courses of chemotherapy differed from that before chemotherapy (P < 0.05). High-sensitivity cardiac TnI (hs-cTnI) and brain-type natriuretic peptide (BNP) increased over time. Further comparison showed that the levels of hs-cTnI (P < 0.05) and BNP (P < 0.05) differed between T4 and T0. The Tei index had a certain predictive value for early cardiotoxicity, with an area under the curve (AUC) of 0.867.Conclusion: In patients with EBC, cumulative anthracycline use of > 4 cycles, trastuzumab use and radiotherapy independently increased 5-year cardiotoxicity (adjusted odds ratio > 3), whereas a Tei index of > 0.40 predicted early subclinical injury with an AUC of 0.867. The cardiotoxicity associated with targeted therapy drugs, represented by trastuzumab, is mostly asymptomatic left ventricular ejection fraction reduction and shows a synergistic effect with anthracyclines. During chemotherapy, the Tei index was more accurate in evaluating myocardial injury.Keywords: chemotherapy, breast cancer, cardiotoxicity, risk factors, predictors